Exfoliation rate of mammary epithelial cells in milk on bovine mastitis caused by Staphylococcus aureus is associated with bacterial load - Nagasawa, Yuya; Kiku, Yoshio; Sugawara, Kazue; Tanabe, Fuyuko; Hayashi, Tomohito (Animal science journal, 2018)
The exfoliation rate of mammary epithelial cells (MECs) in milk is affected by physiological, breeding and environmental factors. Little is known about the relationship between the MEC exfoliation into milk and mammary‐infected Staphylococcus aureus (S. aureus) load on bovine mastitis caused by S. aureus. The aim of this study was to investigate the relationship between S. aureus load and the proportion of MEC exfoliation in milk using five substantial bovine mastitis models. In 64 randomly extracted milk samples from udders at 3–21 days after S. aureus infusion, there were various samples with different numbers of S. aureus counts and somatic cell counts. No significant correlations were found between the S. aureus counts and somatic cell count (r = 0.338). In contrast, a significant correlation was noted between S. aureus counts and the proportion of cytokeratin‐positive cells in the milk from the infused udders (r = 0.734, P < 0.01). In conclusion, the increasing MEC exfoliation rate in milk from mastitis udders caused by S. aureus may contribute to reduced milk yield.